QUANTITATIVE ANALYSIS OF AMORPHOUS CALCIUM CARBONATE PRECIPITATE WITH THE PRESENCE OF ALUMINA IN THE FLOW WATER - S. Raharjo (Universitas Muhammadiyah Semarang, 2017)
Scale of calcium carbonate deposited on the pipe wall was investigatedin the present study. In the experimental work, the scale-forming solution was prepared by mixing equimolar solutions of CaCl2 and Na2CO3. The alumina was selected to inhibit the crystal growth. The scale growth was continuously observed by measuring the conductivity of the solution coming out of the pipe. Scale formed was then evaluated using SEM/EDX analysis. The result showed that the scale has a plate like morphology and the crystalline phase of the scale was found to be mostly calcite. The presence of alumina seems to change the morphology of the crystals from calcite into vaterite and aragonite amorphous. Keywords: simulator scale,calcium carbonate,alumina, amorphous